A comparison of variability in ground reaction force and knee angle patterns between male and female athletes - Breen, S.; Hanlon, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of the present study was to compare the variability of movement and force production in males and females during a diagonal reaction task. Male (n=8) and female (n=8) subjects performed an unanticipated diagonal side cut task eight times with a 90s rest interval between trials. Variability of dominant limb knee angle and ground reaction forces were calculated for each subject over the eight trials. No significant differences were reported between genders for variability in any of the four parameters. This indicates that the variability of sagittal plane knee movement and ground reaction force patterns is not to be related to the increased incidence of anterior cruciate ligament injury in females.